2014
DOI: 10.1111/pde.12469
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Pearly Penile Papules with Carbon Dioxide Laser Resurfacing After Local Anesthesia in an Adolescent Patient

Abstract: Pearly penile papules (PPP) can cause significant psychological morbidity. Herein we report the successful use of a macrofractionated carbon dioxide laser at full-field ablative density settings for the treatment of PPP in a 17-year-old boy using local anesthetic alone. Our experience leads us to believe that PPP can be successfully treated in the pediatric and adolescent populations using this novel and relatively noninvasive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Fully and fractionally ablative CO 2 laser can be performed when treating PPPs (Table 1). 1,13 -18 Fractional ablative CO 2 lasers, when compared with nonfractioned ablative lasers, are associated with a decreased risk of complications like infection, erosions, ulceration, scarring, and postinflammatory dyspigmentation. Fractional therapy also has the added benefit of shortened healing time, which translates into less downtime for the patient post-treatment.…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fully and fractionally ablative CO 2 laser can be performed when treating PPPs (Table 1). 1,13 -18 Fractional ablative CO 2 lasers, when compared with nonfractioned ablative lasers, are associated with a decreased risk of complications like infection, erosions, ulceration, scarring, and postinflammatory dyspigmentation. Fractional therapy also has the added benefit of shortened healing time, which translates into less downtime for the patient post-treatment.…”
Section: Treatmentsmentioning
confidence: 99%
“…Fractional therapy also has the added benefit of shortened healing time, which translates into less downtime for the patient post-treatment. 1,13,14,18…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous wave mode of the CO 2 laser provides better hemostasis and operative field visualization than the short pulse mode (McKinlay, Graham, & Ross, 1999). Using the fractionated CO 2 laser, one group reported more than 90% resolution after a single treatment (Krakowski, Feldstein, & Shumaker, 2015). Another group concluded that two to three treatments were sufficient to completely resolve lesions without adverse effects in both light and dark skin types (Gan & Graber, 2015).…”
Section: Treatmentmentioning
confidence: 99%
“…Another group concluded that two to three treatments were sufficient to completely resolve lesions without adverse effects in both light and dark skin types (Gan & Graber, 2015). While the CO 2 laser exposes the underlying tissue, reepithelialization generally occurs within 5 to 7 days (Krakowski et al, 2015). Nevertheless, the procedure requires anesthesia and increases the risk of scarring and infection.…”
Section: Treatmentmentioning
confidence: 99%